A presença do analista no hospital geral e o manejo da transferência em situação de urgência subjetiva - Glauco Batista (2014)
Modern medicine increasingly based on techno-science is based on a logic that excludes the subject as subjectivity. However, by the very fact of an agreement does not exist between the physician, the patient and the analyst as to the meaning given to trauma, and does not have as eliminate helplessness and own finitude admitted to a hospital patient, deadlock situations always involved and the subjective dimension breaks, at which summons the psychoanalyst to solve the problem. From this point, it becomes a matter worthy of reflection the place the analyst occupy in the general hospital, the nature of its insertion into the staff as well as the power of his performance and where it operates. In this perspective, this study aimed to give greater accuracy to the notion of subjective urgency and its related concepts: trauma, anxiety, panic and helplessness. In addition, to articulate the concept of transference to the subjective urgency in order to give rise to creativity and complicity of the analyst so that it can sustain the necessary space for subjectivity emerge in the hospital. The method used to achieve these objectives was the literature review and case study. The results of this research imply that the position of the analyst in a hospital staff is of the order of a construction and only made possible because of the establishment of the transference. This is because in the psychoanalytic field, that it is always a gamble in this specific case, how the medical staff react to the emergence of subjectivity: with a demand to know about it, or with a request for trouble solution?